Risk factors for infarct expansion are different between lacunar and giant lacunar infarction. (January 2020) - Sato, Takeo; Sakai, Kenichiro; Komatsu, Teppei; Sakuta, Kenichi; Terasawa, Yuka; Omoto, Shusaku; Mitsumura, Hidetaka; Iguchi, Yasuyuki
Abstract: Background and aims: The precise mechanisms underlying the expansion of lacunar and giant lacunar infarction remain unclear. We aimed to determine risk factors for lacunar and giant lacunar infarction and to clarify differences in pathophysiological mechanisms for these two groups. Methods: Patients were selected from a comprehensive stroke center with ≤24 h from onset to initial magnetic resonance imaging with lacunar and giant lacunar infarction. All patients underwent a second magnetic resonance imaging during hospitalization. Infarct size was calculated and compared by the positive region on diffusion-weighted imaging. Factors related to infarct expansion were evaluated separately in the two groups. Results: We screened 1558 consecutive ischemic stroke patients, including 154 patients with small vessel disease (lacunar infarction, 81 patients; giant lacunar infarction, 73 patients). Age (odds ratio (OR), 0.899; 95% confidence interval (CI), 0.824–0.981, p = 0.016), higher cardio-ankle vascular index (OR, 6.011; 95%CI, 2.319–15.581, p < 0.001), higher uric acid (OR, 2.584; 95%CI, 1.091–6.121, p = 0.031), and lower/normal low-density lipoprotein (LDL)-cholesterol (OR, 0.718; 95%CI, 0.557–0.926, p = 0.011) were independently associated with infarct expansion in lacunar infarction patients. Concerning giant lacunar infarction, higher LDL-cholesterol (OR 1.509, 95%CI 1.083–2.103; p = 0.015) and lower/normal body mass index (OR 0.725, 95%CI 0.567–0.926; p = 0.010) were factors independently associated with infarct expansion. Conclusions: Risk factors for infarct expansion differed between lacunar and giant lacunar infarction. The underlying pathophysiological mechanisms for infarct expansion in these two groups should be recognized individually. Graphical abstract: Image 1 Highlights: Pathophysiological changes must differ between lacunar and giant infarct (LI/GLI). High CAVI and uric acid were associated with infarct expansion in LI. High LDL-C and low/normal BMI were associated with infarct expansion in GLI. The mechanisms underlying LI and GLI should be recognized individually.